Aqueous phase properties on governing particle coagulation and mechanism nucleation in one-step emulsion polymerization of styrene. Issue 3 (3rd March 2020) - Liu, Baijun; Jiang, Fuquan; Chen, Jiayu; Han, Ye; Bai, Yang; Zhang, Mingyao
Abstract: As is well known, changing continuous phase properties has a great influence on the nucleation mechanism and particle size, and the addition of electrolytes or alcohol is the main mean to control the properties of solution phase. In this study, a series of experiments about polystyrene emulsion polymerization were produced by adding K2 CO3 and alcohols in different types and contents, so as to study the essential reasons for the influence of solution phase properties on the growth process of particles and the synergistic effect between electrolytes and alcohols. In the presence of methanol-water polymerization systems, the particle size of polystyrene latex particles was enlarged obviously with the increase of methanol content when 0.6 wt% K2 CO3 was contained, but there are no significant changes for the particle size with 0.1 wt% K2 CO3 . For the alcohols with different chain lengths, the particle diameters as follows: Dpropanol (212.6 nm) > Dethanol (123.1 nm) > Dmethanol (90.75 nm). They indicate that adding alcohol to the solution could promote particle coagulation by reducing dielectric constant of the continuous phase. As a result, the polystyrene latex particles with large-scale particle size can be acquired using controlling particle coagulation by changing aqueous phase composition.